Unrecorded Scottish Wood Carvings - Richardson, James S (Proceedings of the Society of Antiquaries of Scotland, 1926)
The article presents a gazetteer of lesser known examples of medieval Scottish wood carving from across Scotland. Items of both Gothic and Renaissance character are considered. The objects include carved panels in churches, aumbrie doors and railings.